Development and Validation of a Deep Learning Radiomics Model Predicting Lymph Node Status in Operable Cervical Cancer - Dong, Taotao; Yang, Chun; Cui, Baoxia; Zhang, Ting; Sun, Xiubin; Song, Kun; Wang, Linlin; Kong, Beihua; Yang, Xingsheng (Frontiers in Oncology, 2020)
Aim: To develop and validate a deep learning radiomics model, which could predict the lymph node metastases preoperatively in cervical cancer patients. Patients and methods: We included a cohort of 226 pathological proven operable cervical cancer patients in two academic medical institutions from December 2014 to November 2017. 5 radiomic features were selected and a radiomic signature was established. We then combined these 5 radiomic features with the preoperative tumor histology and grade of these patients together. Baseline logistic regression model (LRM) and support vector machine model (SVM) were established for the comparison. We then explored the performance of a deep neural network (DNN), which is a popular deep learning model nowadays. Finally, performance of this DNN was validated in another independent test set including 50 cases of operable cervical cancer patients. Results: 1045 radiomic features were extracted for each patient. 28 features were found to be significantly correlated with the lymph node status in these patients (P<0.05). 5 radiomic features were further selected for further study due to their higher predictive powers. Baseline LRM incorporating these 5 radiomic and 2 clinicopathological features was established, which had an area under receiver operating characteristic curve (ROC) of 0.7372 and an accuracy of 89.20%. The established DNN model had 4 neural layers, in which layer there were 10 neurons. Adagrad optimizer and 1500 iterations were used in training. The trained DNN had an area under curve (AUC) of 0.99 and an accuracy of 97.16% in the internal validation. To exclude the overfitting, independent external validation was also performed. AUC and accuracy in test set could still retain 0.90 and 92.00% respectively. Conclusion: This study used deep learning method to provide a comprehensive predictive model using preoperative CT images, tumor histology and grade in cervical cancer patients. This model showed an acceptable accuracy in the prediction of lymph node status in cervical cancer. Our model may help identifying those patients who could benefit a lot from radiation therapy rather than primary hysterectomy surgery if this model could resist strict testing of future randomized controlled trials (RCTs).